The Role of PSL(2, 7) in M‐theory: M2‐Branes, Englert Equation and the Septuples. Issue 5 (29th March 2019) - Cerchiai, Bianca Letizia; Fré, Pietro; Trigiante, Mario
Abstract: Reconsidering the M2‐brane solutions of d = 11 supergravity with a transverse Englert flux introduced by one of us in 2016, we present a new purely group theoretical algorithm to solve Englert equation based on a specific embedding of the PSL(2, 7) group into Weyl [ e 7 ] . The aforementioned embedding is singled out by the identification of PSL(2, 7) with the automorphism group of the Fano plane. Relying on the revealed intrinsic PSL(2, 7) symmetry of Englert equation and on the new algorithm we present an exhaustive classification of Englert fluxes. The residual supersymmetries of the corresponding M2‐brane solutions associated with the first of the 8 classes into which we have partitioned Englert fluxes are exhaustively analyzed and we show that all residual d = 3 supersymmetries with N ∈ 1, 2, 3, 4, 5, 6 are available. Our constructions correspond to a particular case in the category of M2‐brane solutions with transverse self‐dual fluxes. Abstract : Reconsidering the M2‐brane solutions of d = 11 supergravity with a transverse Englert flux introduced by one of the authors in 2016, the paper presents a new purely group theoretical algorithm to solve Englert equation based on a specific embedding of the PSL(2, 7) group into Weyl [ e 7 ] . The aforementioned embedding is singled out by the identification of PSL(2, 7) with the automorphism group of the Fano plane. Relying on the revealed intrinsic PSL(2, 7) symmetry of Englert equation and on the new algorithm the authors present an exhaustive classification of Englert fluxes. The residual supersymmetries of the corresponding M2‐brane solutions associated with the first of the 8 classes into which one has partitioned Englert fluxes are exhaustively analyzed and is is shown that all residual d = 3 supersymmetries with N ∈ 1, 2, 3, 4, 5, 6 are available. The constructions correspond to a particular case in the category of M2‐brane solutions with transverse self‐dual fluxes.